Computational fluid dynamics modelling of quasi-collimated beam apparatus – a typical bench scale UV apparatus for water treatment - Junfeng Lian (IWA Publishing, 2021)
Quasi-collimated beam apparatus (QCBA), a typical bench scale UV apparatus, is crucial for the biodosimetry determination of UV dose in target reactors. However, the key parameters for the QCBA construction are usually estimated via rule-of-thumb calculations. Computational fluid dynamics models are applied in this study to simulate the UV fluence rate (FR) distributions in QCBAs. QCBAs with either a cylindrical tube or successive apertures irradiate quasi parallel light into selected dishes. The simulated Petri factors (PF) in the target QCBAs with a single aperture were all >0.84, and increased with the extended distance (L1) from the UV lamp to the upper aperture. QCBAs with two successive apertures are recommended compared with those with three apertures or cylindrical tube. A trend of FR distribution from dispersed to concentrated is observed when L1 or the interval distance between each aperture increases in a dual-aperture QCBA. QCBAs with multiple lamps were favorable to increase the UV output power, while having a nearly negligible loss of parallelism. An actual QCBA was constructed, and the maximal and average FR and PF values in a 60-mm dish were 0.159 and 0.164 W/m2, and 0.967, respectively, in accordance with the simulated results. HIGHLIGHTS The designed collimator diameter should be larger than the reactor diameter.; FR distributions transformed from dispersed to concentrated when the distance between the lamp and the collimator increased.; QCBAs with two successive apertures were enough to produce satisfactory parallel beams.; QCBAs with multiple lamps were favorable to increase the UV output power with a nearly negligible loss of parallelism.;